Are New Residential Areas Cooler than Older Ones? - Ryoichi Doi (Emerging Science Journal, 2022)
This study was conducted to investigate if passive cooling technologies have been implemented in commercially supplied new residential areas in Bangkok and to observe if there were significant differences in the land surface temperature (LST) compared to old residential areas. Values of LST were compared among 62 residential areas that differed in completion year. The mean LST for the most recent residential areas completed in 2013 or later was significantly less than that for the other older categories, suggesting that passive cooling effects were significantly better functioning in the new residential areas. A roof treatment on old buildings in a public housing project was still quantitatively effective after 8 years. This suggested the possibility of a deteriorated cooling function in the older categories among the residential areas. The possibility of deterioration was quantitatively investigated. The results stressed the importance of the periodic maintenance of passive cooling functions. As an extension of precise basic studies, this is the first study to quantify the passive cooling effects on commercially supplied residential areas. In terms of spatial extent, this residential area–scale study bridges precise analyses of single buildings/materials and regional observations, mainly relying on satellite data. The study results can aid in the mitigation and prevention of the urban heat island phenomenon. Doi: 10.28991/ESJ-2022-06-06-08 Full Text: PDF